FACTORS AFFECTING PERSONAL TAXPAYER COMPLIANCE WITH SANCTIONS AS MODERATING VARIABLES AT EAST MEDAN KPP - Angel Barus, John; Yahya, Idhar; Rujiman, Rujiman (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to examine and analyze the factors that can affect the compliance of individual taxpayers at the Pratama Medan Timur Tax Service Office with sanctions as moderating variables. This study uses primary data with a sample of 99 individual taxpayers using purposive sampling method. The data analysis technique used multiple linear regression analysis using a data processing application program, namely Stata 14. This research was carried out at the Pratama Tax Service Office in East Medan. The results of this study indicate that tax socialization, tax services, tax audits and taxpayer awareness have a positive and significant effect on individual taxpayer compliance. Sanctions as moderating partially are not able to moderate the effect of tax socialization and tax services on individual taxpayer compliance, meanwhile sanctions as moderators are partially able to moderate the effect of tax audits on individual taxpayer compliance in the East Medan Pratama tax service office. Sanctions as moderating partially are able to moderate the effect of taxpayer awareness on individual taxpayer compliance in the East Medan Pratama tax service office.